Copy number variation in salivary amylase: A participant-based study on genetic variation. - Phillips, E. (The Young Researcher)
Amylase (AMY1) is an enzyme found in the mouth that is used to help digest carbohydrates. It has been found that the copy number of AMY1 has been positively associated with protein levels within an individual and also that individual’s population. This information can correspond to the positive ancestral linkage of high starch consumption within agricultural and hunter-gatherer societies. A high starch consumption means that the AMY1 enzyme will be more prevalent within their bodies, and the presence of AMY1 could both help bodies process starches better and prevent future conditions or intestinal diseases. The amylase gene is conclusively connected to the AMY1 copy number production. I hypothesized that individuals within a population will have a similar copy number of the AMY1 gene to each other. Twenty-five high school students located in Norman, Oklahoma were asked to retrieve buccal swabs from the inside of their cheek. DNA then was abstracted from these samples, and a quantitative polymerase chain reaction (qPCR), a machine used to detect the amount of genetic material found in the DNA, was completed in order to determine the copy number within each salivary sample. The qPCR was completed two different times in order to ensure correct results when the data was presented. Results indicated that the copy number within the population were similar to each other, and ranged from 1-12. This means that individuals located in this population have a lower production of amylase, and this provides indication that they are more likely to become obese than in previous research papers located in Arizona. Research shows that a smaller production of AMY1 may contribute to the chances of obesity in the future.